New process to obtain unslaked lime through microwave hybrid heating and its fluid dynamics computational modeling - Breno Henrique Booz Carvalho Corrêa; Juan Canellas Bosch Neto; Alexandre Bôscaro França; Ana Clara Cassin Cordeiro (The Journal of Engineering and Exact Sciences)
This study aimed to analyze the advantages of limestone calcination through a conventional microwave heating technique. For such a purpose, the microwave was merged by hybrid heating and a refractory ceramic internally coated with copper oxide was used with a conventional muffle furnace. It has also been analyzed the behavior of calcining limestone with different masses and variations in retention time using a muffle furnace and microwaves, both with and without using the refractory ceramic. Afterwards, the process has been modeled so as to analyze temperature versus retention time. As a result, calcination using a microwave susceptor with the refractory ceramic substance proved to be a process that takes 35% less time than conventional methods. Furthermore, there has been a reduction in 66.1% of energy expenditure. It was also observed that the new procedure offers advantages in reduced greenhouse gases emissions on account of  the release of only a single substance, ease of air treatment in industrial environments and being a more economically viable process for limestone calcination, which can be further utilized by companies belonging to such a sector. Its patent deposit number BR 202018073002-4 U2 in INPI.